2022
DOI: 10.1159/000522331
|View full text |Cite
|
Sign up to set email alerts
|

The Citrullination-Neutrophil Extracellular Trap Axis in Chronic Diseases

Abstract: Citrullination of proteins is crucial for the formation of neutrophil extracellular traps (NETs) – strands of nuclear DNA expulsed in the extracellular environment along with antimicrobial proteins in order to halt the spread of pathogens. Paradoxically, NETs may be immunogenic and contribute to inflammation. It is known that for the externalization of DNA, a group of enzymes called peptidyl arginine deiminases (PADs) is required. Current research often looks at citrullination, NET formation, PAD overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 273 publications
0
2
0
Order By: Relevance
“…Neutrophils also contribute to immune surveillance by forming neutrophil extracellular traps (NETs), web-like structures composed of DNA and antimicrobial proteins, which can capture and neutralize pathogens, including HBV[ 56 ]. For example, Maronek and Gardlik[ 57 ] explained that patients diagnosed with liver cirrhosis demonstrate a reduced capacity of neutrophils to discharge NETs. This impairment concomitates a decline in CD69 and CD80 expression.…”
Section: Possible Immunological Mechanisms Of Hbv Reactivationmentioning
confidence: 99%
“…Neutrophils also contribute to immune surveillance by forming neutrophil extracellular traps (NETs), web-like structures composed of DNA and antimicrobial proteins, which can capture and neutralize pathogens, including HBV[ 56 ]. For example, Maronek and Gardlik[ 57 ] explained that patients diagnosed with liver cirrhosis demonstrate a reduced capacity of neutrophils to discharge NETs. This impairment concomitates a decline in CD69 and CD80 expression.…”
Section: Possible Immunological Mechanisms Of Hbv Reactivationmentioning
confidence: 99%
“…PAD2 and PAD4 are the two main isozymes determined to mediate citrullination in RA, both of which have been localized in neutrophils [102]. Inflammation is one of the trademark characteristics of RA and results from atypical citrullination, which promotes the formation of NETs, a network of extracellular strings of DNA that bind pathogenic microbes [103,104]. It has also been found that citrullinated histones from neutrophils were routinely targeted by ACPAs, suggesting that increased histone citrullination could be linked to increased autoimmune response [105].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%